Gastric Penetration of Amoxicillin in a Human Helicobacter pylori-Infected Xenograft Model - Lozniewski, Alain (American Society for Microbiology, 1999)
The delivery of antibiotics into Helicobacter pylori-infected human stomachs is still poorly understood. Human embryonic gastric xenografts in nude mice have recently been proposed as a new model for the study of H. pylori infection. Using this model, we compared the penetration of amoxicillin, after intraperitoneal administration of a dose of 20 mg/kg of body weight, into the gastric mucosae of infected and uninfected xenografts. The concentrations of this drug in serum and superficial gastric mucosae were determined at 20 min and 1 and 3 h after injection. Ten mice with H. pylori-infected grafts (n = 5) or uninfected grafts (n = 5) were studied. Mucosal samples were obtained by cryomicrotomy. The concentrations in serum were similar to those obtained in the serum of humans after oral administration of 1 g of amoxicillin. The mean area under the tissue concentration-versus-time curve from 0 to 3 h obtained for mice with infected grafts was significantly higher than that obtained for the animals with uninfected grafts (P = 0.01). These results suggest that the penetration of amoxicillin into the superficial gastric mucosa may be substantially increased in the case of H. pylori infection. Thus, human xenografts in nude mice represent a new, well-standardized model for investigation of systemic delivery of drugs into H. pylori-infected gastric mucosa.